The Effect of Lavender Inhalation Aromatherapy on Sleep Quality of the Elderly at Tresna Werdha Social Institution Jambi City - Permatha, Rhury Nia (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: This study was to determine the effect of lavender inhalation aromatherapy on the sleep quality of the elderly living at Tresna Werdha Social Institution in Jambi City. Methods: This was a quasi-experimental research with 45 participants in the intervention group and 45 in the control group of the elderly. Sleep quality disorders were measured using the Pittsburgh Sleep Quality Index (PSQI). Univariate analysis and bivariate analysis with t-tes t. Result: Disruption of sleep quality in the post-test intervention group (5.31+0.793) was lower than in the pre-test (9.91 + 2.548). Sleep efficiency disturbances are the least affected by interventions. There was a significant difference between the pre-and post-intervention groups, with p-value = 0.00. Conclusion: This suggests that lavender inhalation may be particularly helpful in poor quality of sleep among the elderly. The study highlights the need for further research to explore optimal protocols for administering lavender inhalation aromatherapy, including dosage, duration, and frequency, to maximize its benefits on sleep quality among elderly populations. Additionally, investigating the long-term effects and safety of this intervention would be valuable for its integration into healthcare practices.